#### Answer

LCD=4(x-3)(x-3)=4$(x-3)^{2}$

#### Work Step by Step

$\frac{19x+5}{4x-12}$, $\frac{3}{2x^{2}-12x+18}$
2$x^{2}$-12x+18=2$x^{2}$-6x-6x+18=2x(x-3)-6(x-3)=
=(2x-6)(x-3)=2(x-3)(x-3)
4x-12=(4)x)-(4)(3)=4(x-3)
LCD=4(x-3)(x-3)=4$(x-3)^{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

LCD=4(x-3)(x-3)=4$(x-3)^{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.